Archetype Of Hero In Karakalpak Literature (Based On The Heroic Epic “Alpamys”) - Ubbiniyazova Jamila Turikmenbaevna (International Journal Of Literature And Languages, 2025)
The Turkic epic incorporates a vast body of oral folk tradition, including tales, myths, and legends that reflect the history, culture, and worldview of the Turkic peoples. This article addresses the issue of the hero archetype in the Karakalpak epic “Alpamys”. In this epic, the hero archetype is embodied through the universal model of the “hero’s journey”. The presence of trickster traits in the protagonist contributes to the complexity and multidimensionality of the image and determines the dual nature of Alpamys.